A proposal to improve ray launching techniques (2018)
In this letter, we demonstrate the implementation of an algorithm to model three-dimensional ray launching. A fixed-size reception sphere and cylinder are used in conjunction with numerical methods to simulate multipath propagation with reduced computational time, while retaining the accuracy. This approach was implemented in two office environments that were validated previously by the authors in different simulations. The mathematical feasibility of this method in these applications is demonstrated and the obtained results are discussed. The proposed method has been previously validated by the authors in different simulations as depicted in the references.